Student’s Engagement in Listening through Movies - Safira, Nisrina Zatin; Mulyadi, Dodi; Wijayatiningsih, Testiana Deni (Proceedings Series on Social Sciences & Humanities, 2025)
Listening is an important part of English learning that students need; the purpose of this study is to prove that students need something interesting in listening to lessons. Students can improve their listening skills through movie media because it can attract their attention, preventing them from feeling bored. This research uses a quantitative method. We surveyed 30 students from the English Education Department through surveys after they participated in movie-based listening sessions. The results showed that students were more interested, focused, and motivated when learning with movies compared to regular listening materials. Most students agreed that movies helped them understand spoken English better since they provide context and show how people naturally speak. Overall, adding movies to listening lessons can be a great way to increase engagement and enhance listening skills in EFL classrooms.